2001
DOI: 10.1093/jnen/60.12.1190
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the JNK/p38 Pathway Occurs in Diseases Characterized by Tau Protein Pathology and Is Related to Tau Phosphorylation But Not to Apoptosis

Abstract: JNK and p38, two members of the MAP kinase family, are strongly induced by various stresses including oxidative stress and have been involved in regulation of apoptosis. As both kinases phosphorylate tau protein in vitro, we have investigated their immunohistochemical localization in a group of neurodegenerative diseases characterized by intracellular deposits of hyperphosphorylated tau. Cases included Alzheimer disease, Pick disease, progressive supranuclear palsy, corticobasal degeneration, Gerstmann-Sträuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
110
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(122 citation statements)
references
References 39 publications
11
110
1
Order By: Relevance
“…Specifically, we found that KLC1 deletion induced early and selective transport defects of kinesin-1 cargos and increased activation of the axonal JNK stress kinase pathway, a hallmark of axonal injury (Kenney and Kocsis, 1998;Cavalli et al, 2005), and NFT formation in AD (Atzori et al, 2001;Pei et al, 2001;Lagalwar et al, 2006). Thus, cytoskeletal disorganization through JNK-mediated tau hyperphosphorylation might auto-enhance by inducing additional and severe blockages and swellings (Chang et al, 2003).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Specifically, we found that KLC1 deletion induced early and selective transport defects of kinesin-1 cargos and increased activation of the axonal JNK stress kinase pathway, a hallmark of axonal injury (Kenney and Kocsis, 1998;Cavalli et al, 2005), and NFT formation in AD (Atzori et al, 2001;Pei et al, 2001;Lagalwar et al, 2006). Thus, cytoskeletal disorganization through JNK-mediated tau hyperphosphorylation might auto-enhance by inducing additional and severe blockages and swellings (Chang et al, 2003).…”
Section: Discussionmentioning
confidence: 90%
“…The combined action of several kinases leads to tau phosphorylation at Ͼ20 residues and in different subcellular compartments (Hanger et al, 1998;Buée et al, 2000). Among these kinases, axonal stress activated kinases can phosphorylate tau in vivo and in vitro (Goedert et al, 1997;Reynolds et al, 1997;Chang et al, 2003;Yoshida et al, 2004), and c-jun N-terminal stress kinase (JNK) deposits that precede tau inclusions have been suggested to be caused by early signaling deregulation events in the pathological cascade of cytoskeletal disorganization (Atzori et al, 2001;Lagalwar et al, 2006). The possibility that axonal transport impairments might induce the initiating events that lead to stress kinase activation and tau pathology has been suggested by two recent findings: (1) KLC1 reduction can exacerbate axonal pathologies and amyloid ␤ (A␤) plaque deposition in mouse models of AD generated by amyloid precursor protein (APP) overexpression (Stokin et al, 2005), and (2) axonal transport mediates stress kinase signaling induced by neuronal damage (Cavalli et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Specially, we measured the activated forms of cdk5, GSK-3␤, p38 -MAPK, and JNK because these kinases are known to phosphorylate tau in vitro and in vivo (Atzori et al, 2001;Savage et al, 2002;Sun et al, 2002;Liu et al, 2003). Among them, the activities of GSK-3␤, p38 -MAPK, and JNK are all regulated via phosphorylation at specific amino acids.…”
Section: Lps-induced Inflammation Exacerbates Tau Pathology Via Cdk5mentioning
confidence: 99%
“…Activation of the p38 MAPK pathway has been linked to inflammatory pathology both in AD and in mouse models of the disease (20 -23). In addition, A␤ activates p38 MAPK in cultured microglial cells (24). Because MK2 is an immediate downstream kinase of p38 MAPK, we hypothesized that MK2 itself might play a role in neuroinflammation and neurodegeneration relevant to AD.…”
Section: Studies Using Mk2mentioning
confidence: 99%